Analysis of Groundwater Chemical Characteristics and Spatiotemporal Evolution Trends of Influencing Factors in Southern Beijing Plain - Li, Chen; Men, Bao-Hui; Yin, Shi-Yang (Frontiers in Environmental Science, 2022)
During the rapid urbanisation of Beijing in the past two decades, the original natural underlying surface has been changed, and the groundwater recharge and discharge processes had undergone great changes. Therefore, whether these natural and human factors affect the evolution of groundwater chemical composition, and how these influences evolve, need to be studied urgently. In this study, the Daxing District was taken as a typical area to understand the evolution rules of the chemical characteristics of shallow groundwater in the plain areas of Beijing. By collecting monitoring data on shallow groundwater from 2006 to 2016, the spatiotemporal evolution trends of the chemical characteristics and influencing factors of shallow groundwater in Daxing District were studied using the hydrochemical analysis methods and principal component analysis–partial connection number method. The results show the following: 1) The cations and anions of groundwater in the study area increased with time, indicating that the groundwater quality tends to deteriorate. 2) The hydrochemical type and anion and cation components changed accordingly with the change in NO3−, indicating the profound impact of NO3− on the evolution of groundwater components. 3) The groundwater has always been affected by human factors and natural factors. Natural factors have dominated, but the influence of human factors on hydrochemical components has been increasing. From the spatial distribution of the impact of human factors and natural factors on groundwater composition, regions with higher urbanisation degrees are highly affected by human factors and vice versa. This study can provide a theoretical and methodological reference for regional groundwater management and industrial layout.